A framework for project management implementation process for improving the business performance of small and medium enterprises in the United Arab Emirates - Mohammed Almulla Alshehhi, Abdulnaser Abdulla (2022)
Even though the SME sector in the UAE accounts for 95%, growth of the SMEs faces different issues for the manager to deal with and the majority of SMEs in the country are usually managed by the traditional management techniques. Hence, this study aims to identify the factors influencing the project management process towards the business performance of SMEs, to determine the relationship between these identified factors in the project management process and business performance of SMEs, and to establish an improved framework for project management implementation process with the business performance of SMEs in the United Arab Emirates (UAE). This research employed the quantitative research design. Also, the SMEs selected for this study are from all the states within the United Arab Emirates (UAE). Since the total population number of SMEs in the UAE is 4000 that comes from the construction industry, the sample size of this study is 260 determined based on the Krejcie and Morgan’s (1970) study. The data distribution box plot was checked and 23 outliers were identified from the 391 questionnaires that were distributed. Only 260 respondents (cases) were used for statistical analysis using SPSS version 23 for the exploratory factor analysis (EFA) and confirmation factor analysis (CFA) by the practice of AMOS that was embraced. The findings of the research research object led the identification of four project management process factors, which are project risk management, project scope management, project cost management, and project communication management. The findings of the research objective showed that these four independent variables (project risk management, project scope management, project cost management, and project communication management) have a significant effect on the performance of SMEs with P-values 0.003, 0.000, 0.000 and 0.000, respectively. Also, the third research objective led to the framework that utilises project process management factors to enhance the performance of SMEs in the UAE. From the results of this study, the UAE government has several roles to play to assist in the areas of the needed priorities to improve the business performance of SMEs in the UAE.